(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
In this contribution, new data about vascular plants in Ukraine are presented. It includes new records and confirmations for the Ukrainian regions for 82 species: Acer monspessulanum, Aconitum anthora, Amaranthus deflexus, Anthriscus cerefolium, Asplenium ruta–muraria, Arabis alpina, Artemisia argyi, A. sieversiana, A. verlotiorum, Berberis aquifolium, Bolboschoenus glaucus, Calepina irregularis, Centaurea borysthenica, Cephalanthera longifolia, Cirsium esculentum, Clematis vitalba, Coreopsis grandiflora, Corydalis caucasica, C. cava subsp. marschalliana Crithopsis delileana, Cucumis melo, Cydonia oblonga, Cyperus odoratus, Dasypyrum villosum, Dracocephalum ruyschiana, Eragrostis pilosa, Erechtites hieraciifolius, Eriochloa villosa, Euphorbia glyptosperma, E. lathyris, E. prostrata, Fallopia baldschuanica, Ficus carica, Galanthus nivalis, Galium humifusum, Goodyera repens, Gymnocladus dioicus, Hedera helix, Heliotropium stevenianum, Hesperis matronalis subsp. matronalis, Huperzia selago, Hypericum polyphyllum, Iris foetidissima, Lagurus ovatus, Laser trilobum, repens, Limonium alutaceum, Lipandra polysperma, Luzula luzuloides, Nymphoides peltata, Oenothera glazioviana, Opuntia humifusa, Ostericum palustre, Peganum harmala, Peucedanum latifoli-um, Phragmites australis subsp. isiacus, Phytolacca americana, Pilosella flagellaris, Pistia stratiotes, Platanthera chlorantha, Poa remota, Primu-la vulgaris, Reynoutria × bohemica, Rubus × idaeoides, Salix daphnoides, Saxifraga tridactylites, Schoenoplectus litoralis, Smyrnium perfoliatum, Sorghum halepense, Stellaria neglecta, Symphyotrichum ciliatum, Tragus racemosus, Trifolium incarnatum, T. lupinaster, Tripo-lium pannonicum, Typha domingensis, Veronica argute-serrata, V. car-diocarpa, Vincetoxicum fuscatum, Vitis riparia, Utricularia australis and U. minor. Among them, species of vascular plants are newly reported for large areas including several regions of Ukraine. Most of the findings are new for administrative regions of Ukraine: 14 species are reported for the first time for Kirovohrad Region, 13 – for Zhytomyr Region, 11 – Odesa Region, 7 – Mykolaiv and Zakarpattia regions, 5 – Kherson Region, 4 – Dnipropetrovsk, Kyiv regions, 3 – Rivne, Vinnytsia, Chernihiv regions, two – Ivano-Frankivsk, Lviv, Ternopil, Khmelnytskyi regions and Authonomous Republic of Crimea, 1 – Volyn, Zaporizhzhia, Chernivtsi regions and Kyiv City. The localities of numerous not widely distributed species of vascular plants are provided. Among them, species which are included in the Red Data Book of Ukraine and regionally rare plants.